IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH DALAM MEMBENTUK KARAKTER GEMAR MEMBACA SISWA KELAS IV SD NEGERI PASI ACEH - Lusi Wahdil; , Rida Puspita Sari; Nurjannah; Dian Kristanti (STAI Nusantara Kota Banda Aceh, 2026)
This study aims to describe the implementation of the school literacy movement program in shaping students' love for reading and to describe the supporting and inhibiting factors in implementing the school literacy movement program in shaping the reading habits of fourth-grade students at SD Negeri Pasi Aceh. The type of research used is descriptive research with a qualitative approach. The subjects in this study are the classroom teacher and all fourth-grade students, totaling 12 people. The data collection techniques used in this study are observation, interviews, questionnaires, and documentation. The instruments used to collect data in this study consist of observation sheets, interview sheets, questionnaire sheets, and validation sheets. Based on the research results, it can be concluded that the implementation of the School Literacy Movement (GLS) Program in grade IV of SD Negeri Pasi Aceh has been running well and plays a role in developing students' reading habits. GLS has been effectively carried out through a 15-minute reading activity before lessons, the use of reading corners, and the school library. All students gave positive responses regarding their reading habits, with 58.33% strongly agreeing and 41.67% agreeing. The success of the program is supported by the school's backing, availability of literacy facilities, and student enthusiasm. However, there are still obstacles, such as some students' low interest in reading, lack of family support, and limited implementation time. Therefore, better cooperation between the school, teachers, parents, and students is needed to make GLS more effective in fostering students' reading habits. Keywords: Implementation, School Literacy Movement Program, Students’ Reading Habit Character.